Structural impact mitigation of bridge piers using tuned mass damper. (1st April 2016) - Hoang, Tu; Ducharme, Kevin Thomas; Kim, Yeesock; Okumus, Pinar
Highlights: The first attempt in literature to explore TMD systems in structural impact mitigation. A systematic approach utilizing exhaustive parameter search for structural impact mitigation. The better performance over four benchmark TMD systems for structural impact mitigation. Abstract: This paper proposed the application of tuned mass damper (TMD) systems to bridge piers for structural impact damage mitigation to reduce the risk of collapses. A bridge superstructure and substructure were designed in accordance with The American Association of State Highway and Transportation Officials (AASHTO) Load and Resistance Factor Design (LRFD) Bridge Design Specifications (BDS) (2012). A variety of vessel collision forces were obtained from collision testing of a scaled reinforced concrete pier. The optimal parameters of TMD systems were determined such that the drift and displacement of the bridge superstructure were minimized for various impact scenarios. Structural impact mitigation performance of the pier equipped with the proposed optimal TMD system was compared with four different TMD systems employing the benchmark TMD optimal parameters. The uncontrolled responses were used as a baseline. It was demonstrated from the extensive simulations that the control effectiveness of the proposed TMD system was 25% better than all of the existing TMD models in reducing the response of the structure.